Mobile group blogging in learning: a case study of supporting cultural transition - Shao, Yinjuan (2010)
A mobile group blog is an example of a Web 2.0 social space, as well as a tool for the instant collection of contextual information, the immediate sharing of information and later reflection. Records in the form of multimedia created through mobile blogging can assist people to keep a versatile representation of artefacts they encounter on the move in everyday life. Overseas students are an example of a large group of people whose cultural learning could be supported by this technology. They could share contextual information and their own stories with other people currently experiencing the host culture, as well as people who do not have the opportunity to experience the host culture first-hand. To examine and evaluate how the mobile group blog could be applied in learning, a case study was conducted on involving overseas students. This research explored the suitability, appropriateness and benefits of a mobile group blog in assisting overseas students to manage their culture shock. It illustrates how the mobility of mobile devices assists the capture of contextual information on the move when overseas students start adapting to the new environment. The group blog site provided a platform to share and exchange their experiences and thoughts, as well as a resource of information on authentic cultural transition for future students. Four sub-studies were conducted around this theme. The first two studies investigated the demands and needs of a mobile group blog application in cultural transition. The third study investigated real and practical mobile blogging activities with a group of twelve Chinese overseas students who had newly arrived in Nottingham. The fourth study was conducted in China. In this study, a number of Chinese students who intended to study abroad were asked to evaluate the contents of the mobile group blog created by the twelve Chinese mobloggers in Study three. Findings from the four studies reveal the possibilities, suitability, strengths and weaknesses of the mobile group blog in assisting cultural transition. The thesis also presents positive feedback from participants as well as feedback on the limitations of this application. Then as added value to this research, it also suggests future educational applications of the mobile group blog.